2008
DOI: 10.1159/000113519
|View full text |Cite
|
Sign up to set email alerts
|

Reintroduction of Cow’s Milk in Milk-Allergic Children: Safety and Risk Factors

Abstract: Background: Although development of clinical tolerance is the rule in allergy to cow’s milk (CM), food challenges are required in order to reintroduce CM into the patient’s diet. Less ‘invasive’ procedures able to predict tolerance would be useful as clinical tools. The purpose of this study was to identify potential risk factors for clinical reactivity in CM-allergic children assessed for CM reintroduction. Methods: One hundred and sixteen open challenges performed in children 10–47 months old with IgE-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
1
9
0
2
Order By: Relevance
“…[31][32][33] However, it seems impossible to unambiguously identify patients with systemic reactions to CM only on the basis of IgE reactivity. In this context several recent studies performed with highly purified allergen molecules have shown that IgE reactivity and allergenic activity do not always correlate.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] However, it seems impossible to unambiguously identify patients with systemic reactions to CM only on the basis of IgE reactivity. In this context several recent studies performed with highly purified allergen molecules have shown that IgE reactivity and allergenic activity do not always correlate.…”
Section: Discussionmentioning
confidence: 99%
“…Liao et al compared exclusive breastfeeding in infants and children < 4 months with those ≥ 4 months and showed a decreased risk of sensitization toward CMA up to the age of 2 years in long time breast feeding (20). A high rate (96%) of exclusive breast feeding in this study was the result of the government's effort in the past few years to promote breast feeding.…”
Section: Discussionmentioning
confidence: 60%
“…Skin prick testing with commercial extracts and relevant wines were performed according to standard protocols [9,10]. Any size of wheal larger than the negative control was considered positive.…”
Section: Methodsmentioning
confidence: 99%